2017
DOI: 10.1097/brs.0000000000002136
|View full text |Cite
|
Sign up to set email alerts
|

Quebec Serve and Protect Low Back Pain Study

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
1
8
0
3
Order By: Relevance
“…The online survey software SurveyMonkey® was used to publish the study questionnaire and collect data. Building on the success of previous online studies, 26 , 27 a web‐based dissemination strategy was implemented to reach a community sample of people living with chronic pain. All the advertisements included a hyperlink to the web‐based questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…The online survey software SurveyMonkey® was used to publish the study questionnaire and collect data. Building on the success of previous online studies, 26 , 27 a web‐based dissemination strategy was implemented to reach a community sample of people living with chronic pain. All the advertisements included a hyperlink to the web‐based questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Reports of low back pain from those officers increased with increasing years of work as a police officer [Arts 2006]. Although none of the interviewed officers required transfers or missed work because of back pain, it may impact overall quality of life and career longevity [Douma et al 2017]. All but three of the patrol officers we interviewed reported using the duty belt alone to wear their equipment.…”
Section: B-6mentioning
confidence: 99%
“…An increased length of service to the police department has been associated with recurrent and chronic episodes of low back pain in LEOs [ 13 ]. A large cross-sectional study conducted throughout the Quebec Police Department found that nearly 68% of respondents to a web-based survey reported incidents of low back pain in the past 12 months, and of that 68%, nearly 97% had the perception that their low back pain was related to their work on the police force [ 14 ]. Causes for low back pain range from little lumbar support and wearing a duty belt [ 15 ] to time spent driving, both the number of hours driven and the distance traveled [ 16 ].…”
Section: Introductionmentioning
confidence: 99%